2014
DOI: 10.1590/1809-9823.2014.13123
|View full text |Cite
|
Sign up to set email alerts
|

Poder preditivo do MoCa na avaliação neuropsicológica de pacientes com diagnóstico de demência

Abstract: O estudo teve como objetivo correlacionar testes neuropsicométricos em idosos com mais de quatro anos de escolaridade e avaliar a acurácia do MoCA no diagnóstico da doença de Alzheimer (DA) e comprometimento cognitivo leve (CCL). Foram avaliados 136 idosos atendidos no Instituto de Geriatria e Gerontologia, no período de abril de 2010 a dezembro de 2012. Os instrumentos utilizados foram o Miniexame do Estado Mental (MEEM), Cambridge Cognitive Examination (CAMCOG), teste do Desenho do Relógio (TDR), teste de Fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 39 publications
0
10
0
7
Order By: Relevance
“…On the other hand, 24 articles showed information regarding the discrimination between controlled individuals and individuals with dementia. Fourteen studies (58.3%), demonstrated similar accuracy between MoCA and MMSE in the detection of mild dementia, while the other 10 studies (41.7%) showed MoCA was superior to MMSE for this detection (Cecato et al, 2014;Delgado et al, 2017;Freitas et al, 2013;Fujiwara et al, 2010;Hsu et al, 2015;Janelidze et al, 2017;Lee et al, 2008;Luis et al, 2009;Wang et al, 2013).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…On the other hand, 24 articles showed information regarding the discrimination between controlled individuals and individuals with dementia. Fourteen studies (58.3%), demonstrated similar accuracy between MoCA and MMSE in the detection of mild dementia, while the other 10 studies (41.7%) showed MoCA was superior to MMSE for this detection (Cecato et al, 2014;Delgado et al, 2017;Freitas et al, 2013;Fujiwara et al, 2010;Hsu et al, 2015;Janelidze et al, 2017;Lee et al, 2008;Luis et al, 2009;Wang et al, 2013).…”
Section: Resultsmentioning
confidence: 92%
“…Of the 34 studies selected, 31 showed information regarding the accuracy of MoCA and MMSE in detecting MCI. Twenty five articles (80.6%) showed superiority of MoCA to MMSE in discriminating individuals with mild cognitive impairment and no mild cognitive impairment (Cecato et al, 2014;Chen et al, 2016;Chu et al, 2015;Delgado et al, 2017;Dong et al, 2012;Freitas et al, 2013;Fujiwara et al, 2010;Guo et al, 2010;Horton et al, 2015;Hsu et al, 2015;Hu et al, 2013;Janelidze et al, 2017;Kaya et al, 2014;Lee et al, 2008;Lifshitz et al, 2012;Lu et al 2011;Luis et al, 2009;Magierska et al, 2012;Mellor et al, 2016;Memória et al, 2013;Nasreddine et al, 2005;Roalf et al, 2013Roalf et al, , 2017Saleh et al, 2018;Tan et al, 2015;Tsai et al, 2012Tsai et al, , 2016. In this group of articles are included the two studies with the most sample sizes of this review, with more than 7,000 elderly subjects each, with excellent methodological qualities, evaluated through QUADAS 2 tool (Lu et al, 2011;Tan et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…e eligibility criteria were Functional Ambulation Categories (FAC) ≥ 2 [25], absence of cognitive deficit by Montreal Cognitive Assessment (MoCa), with values higher than 26 [26,27], ability to walk independently 12.4 m to participate in the gait assessment, and absence of physical and/or functional impairment that would limit treadmill walking. Exclusion criteria were the presence of untreated neurological or cardiorespiratory diseases and/or limitation of the ability to walk on the treadmill, incapacitating visual or hearing deficits that would not permit the investigation and the subject's drop-out during any phase of intervention or evaluation.…”
Section: Samplementioning
confidence: 99%
“…Todavia, o declínio cognitivo existe nos diversos transtornos do movimento, já comprovado. E conforme a evolução e a gravidade dos sintomas, pior ele se torna 46,[50][51][52]. Classicamente na literatura não há comparação entre os testes.…”
unclassified